The Role of Women in Political Patronage and Political Alliance in the Joxzin Community Organization in the 2019 Election - Subandi, Yeyen (Jurnal Ilmiah Hubungan Internasional, 2024)
The aim of this research is to look at the role of women in political patronage relationships which resulted in a political alliance between the community organization Joxzin (Jogjakarta Islamic Never Die) and the political party United Development Party (PPP) in the 2019 elections in 2019. Sleman Regency, Special Region of Yogyakarta , Indonesia. Joxzin is a community organization consisting of male and female members. This research uses a convergent method of mixing qualitative and quantitative data which is then analyzed using the NVivo 12 Plus application. The findings obtained in this research are that Joxzin has political patronage ties. Joxzin has resources and power compared to patrons because Joxzin as a client can appoint Ahmad Zahran to be Chairman of the Branch Leadership Council of the Yogyakarta City Development United Party. With Joxzin's strong political alliance, Muhammad Yazid from the Sleman Regency Pilkada became a legislative member of the Yogyakarta Special Region People's Representative Council for the 2019-2024 period. Keywords: Political patronage, political alliances, Woman, Joxzin, Partai Persatuan Pembangunan (PPP).